Metal-complex chromophores for solar hydrogen generation. (3rd November 2016) - Yuan, Yong-Jun; Yu, Zhen-Tao; Chen, Da-Qin; Zou, Zhi-Gang
Abstract : Photoactive metal-complexes with applications in solar energy harvesting have been receiving profound research interest. We present in this exciting area the recent development of metal-complex chromophores as sensitizers and supramolecular photocatalysts to facilitate the conversion of solar energy into chemical hydrogen fuel. Abstract : Solar H2 generation from water has been intensively investigated as a clean method to convert solar energy into hydrogen fuel. During the past few decades, many studies have demonstrated that metal complexes can act as efficient photoactive materials for photocatalytic H2 production. Here, we review the recent progress in the application of metal-complex chromophores to solar-to-H2 conversion, including metal-complex photosensitizers and supramolecular photocatalysts. A brief overview of the fundamental principles of photocatalytic H2 production is given. Then, different metal-complex photosensitizers and supramolecular photocatalysts are introduced in detail, and the most important factors that strictly determine their photocatalytic performance are also discussed. Finally, we illustrate some challenges and opportunities for future research in this promising area.